Additional algae (excluding cyanobacteria) of Bagh-Jhoda wetland, Morang, Nepal - Rajopadhyaya, Ritu; Rai, Shiva Kumar (Nepalese Journal of Biosciences, 2019)
In this paper, a total of 46 additional algae (excluding cyanobacteria) have been described from Bagh-Jhoda wetland, Morang. They belong to 7 classes, 13 orders, 21 families, and 28 genera. Algae were collected from 8 different peripheral localities of the wetland during winter, summer and rainy seasons, 2014. They were collected by squeezing submerged parts of macrophytes and by using plankton mesh net. Cosmarium was the largest genus as usual in the previous studies. The water in this wetland is maintained as it lies along the southern edge of Char-Koshe Jungle, hence harbor rich algal species.